Online Training on Writing Scientific Articles in Early Childhood Education for Accredited Sinta Journals - Syarfina Syarfina; Nindia Anis (Journal of Comunity Service in Early Childhood Education, 2025)
Background: The ability to write scientific articles is an essential competency for Early Childhood Education students, particularly in supporting academic publication in accredited national journals. However, many students still face difficulties in understanding the structure, writing techniques, and publication processes required for scientific articles. This condition indicates the need for structured training programs that can improve students’ scientific writing skills. Aims: This community service program aims to enhance students’ competence in writing scientific articles and preparing manuscripts for accredited national journals. Methods: This program employed a training-based community service approach integrated with mentoring, mediation, and evaluation activities. The implementation was conducted online via Zoom and involved 150 participants from various regions in Indonesia. The program consisted of preparation, implementation, and evaluation stages. The implementation stage included material delivery, hands-on practice, group discussions, and mentoring sessions. Data were collected through observation, documentation, and participant feedback using questionnaires, and analyzed descriptively. Results: The results indicate that the program successfully improved participants’ understanding and skills in scientific article writing. Participants demonstrated increased ability in structuring manuscripts, applying appropriate writing techniques, and revising articles based on reviewer feedback. Evaluation results showed high participant satisfaction, with average scores ranging from 4.5 to 4.8 across various aspects, including material relevance, clarity, and usefulness of practical sessions. Conclusion: The training-based community service program is effective in enhancing students’ scientific writing competence and readiness for publication in accredited journals. The integration of training, practice, mentoring, and evaluation provides meaningful learning experiences and can be applied as a sustainable model for academic capacity development.